تقييم واقع مواقف السيارات العائدة للمباني الحكومية في مدينة اللاذقية - زريق, سامر (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر مشكلة إيجاد مكان مناسب لوقوف السيارات إحدى المشاكل الأساسية التي تعاني منها المدن المتوسط والكبيرة، ومدينة اللاذقية إحدى المدن المتوسطة في سوريا, التي شهدت في السنين الأخيرة زيادة ملحوظة في عدد السكان وتوسع وتطور كبيرين في بنية المدينة، لكن الجزء القديم من المدينة الذي تتركز فيه معظم الدوائر الحكومية والمباني المكتبية، لم يلحظ تصميمها تأمين أماكن مناسبة لوقوف السيارات بحيث لا يتعارض هذا الوقوف مع حركة المركبات والمشاة على السواء. سوف يتعرض هذا البحث لواقع مواقف السيارات في الأبنية الحكومية والمكتبية القائم منها، وما هو قيد الإنشاء، من خلال بحث ميداني يشمل ثلاثين دائرة حكومية ومبنى مكتبي. وقد استخدمت لهذه الغاية استمارة استبيان مكنت من الحصول على معلومات عن المباني المدروسة من حيث المساحة الطابقية وعدد المراجعين والعاملين بالمبنى وعدد مواقف السيارات المتوفر داخل وخارج المبنى...الخ، ومع مقارنة أعداد المواقف المتوفرة مع تلك المعتمدة في المواصفات العائدة لبعض المدن المتوسطة والكبيرة في العالم، تبين أن معظم المباني المدروسة لا تحقق ما أوصت به تلك المواصفات. في نهاية البحث تم تقديم عدد من المقترحات أبرزها ضرورة تأمين أمكنة كافية لوقوف السيارات وفق المواصفات العالمية المعتمدة في مدن مماثلة لمدينة اللاذقية، والبحث في إيجاد معايير محلية تلبي الاحتياجات الحالية والمستقبلية لهذا النوع من الأبنية. Finding a suitable car parking place is considered one of the most common problems in big and median cities. Lattakia is a median city in Syria, which had, in a short time, a noticeable increase in population and it expanded widely, but the design of Governmental and office Buildings (centering in the old part of Lattakia with high rate of demand on parking ) did not take into consideration the importance of car parking to avoid conflict with the movement of vehicles and pedestrians. This research deals with the actual car parking of governmental and office building in Lattakia, by choosing 30 Governmental and office Building (part of which are under execution), through preparating a survey sheet to get information about the area of the Buildings, the number of staff and visitors, number of available car parking inside and outside of the buildings, and comparing with car parking standards of few big and median cities in USA, England..,ect. It showed that most of the buildings do not suit what these standard have involved. Then results and conclusions and final proposals are registered, the most prominent were the necessity of providing enough areaa for car parking, according to the standards used for cities similar to Lattakia city, search must be do in order to find local standards that fulfill the present and future needs for such kind of buildings.